2009
DOI: 10.1136/bcr.03.2009.1641
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic gastroenteritis causing stenosis of bulbo-duodenal junction: medical and endoscopic management

Abstract: Eosinophilic gastroenteritis is a rare disease characterised by tissue eosinophilia that can involve any layer or part of the gut from the oesophagus to the rectum. In Saudi Arabia, the disease has not been reported in the literature before. We report the disease entity as an unusual cause of gastric outlet obstruction. A 50-year-old man was admitted through the gastrointestinal clinic with complaints of epigastric pain associated with dyspepsia for 1 month, and weight loss of 4 kg in 2 months. Examination rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, the duodenum, jejunum, and colon were also involved in this case. Ashraf et al reported a case of EGE causing stenosis of the second and third part of the duodenum (21). EGE was diagnosed by a pathological examination using biopsy specimens after endoscopic dilation in Ashrafs' case.…”
Section: Discussionmentioning
confidence: 99%
“…However, the duodenum, jejunum, and colon were also involved in this case. Ashraf et al reported a case of EGE causing stenosis of the second and third part of the duodenum (21). EGE was diagnosed by a pathological examination using biopsy specimens after endoscopic dilation in Ashrafs' case.…”
Section: Discussionmentioning
confidence: 99%
“…The patient underwent dilation of the stenotic area with a pneumatic balloon in combination with a pharmacological treatment course (i.e., esomeprazol, domperidone, loratadine, and prednisone) (61). This was the first reported case in which the treatment involved an endoscopic intervention for a gastrointestinal tract obstruction due to EG, thereby circumventing the need for surgical resection.…”
Section: A C Bmentioning
confidence: 99%